Merdeka Belajar Building Villages Based On Experience Project Based Learning In Tourism Village Labsite Department Of PLS In The Production Of Youtube Video Learning Media - Zulkarnain Zulkarnain; Kukuh Miroso Raharjo; Edi Widianto (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Accommodating the Free Learning program, the Department of Outdoor Education, Faculty of Education, State University of Malang (UM) actively facilitates students to develop their capabilities through curriculum development and implementation. The UM curriculum was developed and implemented using an experience-based learning approach based on project-based learning through Merdeka Learning Kampus Merdeka through the form of learning activities to build villages. According to Borg and Gall, the Design of Learning Innovation Development uses research development methods. Research Objectives Realizing the independent innovation model of learning to build villages based on experience project based learning in making YouTube video media managing village tourism labsite Department of Out-of-School Education. Conclusion: (1) Free Learning Guide and Innovation Module to Build Villages Based on Experience Project Bsed Learning in Making Youtube Media Management of Labsite Tourism Villages for the Department of Outdoor Education FIP UM has gone through the process of analyzing student learning needs in the independent learning program to build villages as a learning resource and material learning PLS, writing initial drafts of learning materials through making YouTube video media through project learning experience in managing village tourism labsite PLS Department, validating learning media experts and outside school education experts, revising input and suggestions from learning media experts and outside school education experts. (2) Based on data analysis on the results of content assessment and implementation of the use of guides and modules from learning media experts and outside school education experts on learning products through the creation of experience-based project-based learning YouTube video media in the management of labsite tourism villages of the PLS FIP UM Department, valid results were obtained ( no revision)